An Acute Bout of Exercise Suppresses Appetite via Central Lactate Metabolism. (1st February 2023) - Chen, Yi; Zhang, Siyan; Ye, Liu; Chen, Hong; Yu, Lehua; Wu, Dandong
Graphical abstract: Highlights: Acute exercise suppresses food intake. Acute exercise affects hypothalamic Jak2-STAT3 signaling and neuropeptide expression. Central lactate metabolism mediates exercise-induced appetition suppression. Central lactate mediates exercise-induced alterations in Jak2-STAT3 signaling. Central lactate impacts on exercise-induced alterations in neuropeptide expression. Abstract: Exercise has been reported to elicit a transient suppression of appetite. Plasma lactate, which is produced by exercising muscle, is believed to have a critical effect on exercise-induced appetite suppression. However, the underlying mechanisms and signaling steps of central lactate metabolism remain unexplored. After central oxamate administration, C57BL/6J male mice performed 10 high-intensity interval running at 90% Vmax for 4 minutes each, which separated by 2 minutes at 12 m/min. Food intake and the expression of hypothalamic appetite-regulating neuropeptides including proopiomelanocortin (POMC) and neuropeptide Y (NPY) were investigated following exercise training. Janus kinase 2 (Jak2)-signal transducer and activator of transcription 3 (STAT3) signaling pathway was also determined by Western blot. In addition, hypoxia-inducible factor-1α (HIF-1α) was investigated to explore the effect of central lactate metabolism following exercise. We found that central oxamate administration reversed exercise-induced suppression of food intake, and as well as changes in the expression of POMC and NPY. Moreover, acute exercise led to an increase in the phosphorylation of Jak2 and STAT3 in the hypothalamus, while central lactate inhibition significantly blunted this effect. In addition, HIF-1α expression increased obviously after exercise, while it was attenuated by central oxamate administration. Collectively, our data reveal that central lactate metabolism mediates exercise-induced suppression of appetite and changes in neuropeptides, possibly through enhanced Jak2-STAT3 signaling.